Formation of a communicative culture of students in the system of vocational education - Nagymzhanova К.М., Nagymzhanova К.М.; Ahmetbek A.D., Ahmetbek A.D. (Рroblems of engineering and professional education, 2022)
The article is devoted to the specifics of the formation of a future teacher’s communication culture, motivational-value, substantive and personal aspects. It is also noted that the professional readiness of future teachers lies in the fact that their communication is characterized by the use of cultural elements in their teaching activities. It is believed that the education system allows the future teacher to effectively create a communication culture based on: creating a developing educational environment; the use of active forms and teaching methods, in particular trainings, which contribute to the cognitive effectiveness of the educational process. The pedagogical process should be adequate, differentiated and periodic